The Use of Animation Film in Forming Representations about the Planet Earth and the Solar System - SANDA VEREȘ (Romanian Review of Geographical Education, 2020)
This research aims to analyse the process of grasping the Solar System by the students during their learning activities in which we used an animation film and other educ ational means (geographic globe, schematic drawings, 3D model, etc.), as well as the results obtained. In order to achieve this goal, we organized an action-research within Mathematics and Environmental Exploration subject, to the first-grade class, during the lesson “The Solar System”. We sought to identify the criteria based on which the teacher chooses an animated film for a lesson, the ways to effectively use it in learning activities to facilitate the learning process. An experimental group and a control group took part within this action. We conducted three tests, an initial test, a post -watching test, and a test after the formative intervention from the experimental class. During the training experiment, we observed the students’ behaviour and analysed the process of teaching, learning, assessment, and the students’ results. The volume of students’ knowledge about the Solar System increased when the most suitable animation film was used for the given topic and the students were involved in an active learning activity in which they discussed with the teacher the plot of the film, using also other visual materials. We have come to the conclusion that a learning activity making use of animated films and being mediated by the teacher has a greater efficiency in forming representations about the structure of the Solar System and its functioning than an individual viewing of an animated film about the Solar System. The results showed that the students had accurate representations about the Solar System, improved their thinking skills, in terms of scientific understanding, knowledge-implementation, and reasoning ability. The fact that the students watched the animated film about the Solar System and were involved in an active learning activity under their teacher’s guidance can explain the positive results obtained by the students of the experimental group.